Verbal and nominal functional categories of a Turkish speaking autistic child - Günhan, N. Evra. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
Autism is a neuro-developmental disorder which affects social communication and language facilities.The present study investigates the production of nominal and verbal functional categories by a Turkish speaking autistic child. The data which consisti of spontaneous speech samples of the autistic child suggest that the subject differs from his normally developing peers with respect to the projection of nominal and functional categories,The subjectś syntactic development is severely delayed. The subjectś syntactic development is severely delayed. The subjectś grammar show deviances related to verbal and nominal functional categories.
Keywords: Autistic children -- Language.; Autism in children.; Speech disorders in children.